Robust Confidence Intervals for PM2.5 Concentration Measurements in the Ecuadorian Park La Carolina - Wilmar Hernandez; Alfredo Mendez; Rasa Zalakeviciute; Angela Maria Diaz-Marquez (Sensors, 2020)
In this article, robust confidence intervals for PM2.5 (particles with size less than or equal to <semantics> 2.5 μ m </semantics> ) concentration measurements performed in La Carolina Park, Quito, Ecuador, have been built. Different techniques have been applied for the construction of the confidence intervals, and routes around the park and through the middle of it have been used to build the confidence intervals and classify this urban park in accordance with categories established by the Quito air quality index. These intervals have been based on the following estimators: the mean and standard deviation, median and median absolute deviation, median and semi interquartile range, <semantics> a </semantics> -trimmed mean and Winsorized standard error of order <semantics> a </semantics> , location and scale estimators based on the Andrew’s wave, biweight location and scale estimators, and estimators based on the bootstrap- <semantics> t </semantics> method. The results of the classification of the park and its surrounding streets showed that, in terms of air pollution by PM2.5, the park is not at caution levels. The results of the classification of the routes that were followed through the park and its surrounding streets showed that, in terms of air pollution by PM2.5, these routes are at either desirable, acceptable or caution levels. Therefore, this urban park is actually removing or attenuating unwanted PM2.5 concentration measurements.